Atlas of patient-reported outcome measures, nomograms and scoring systems used in simple and complicated urinary tract infections: a systematic review - Nicholas L. Harrison; Arthur W. Day; Zafer Tandogdu; Gernot Bonkat; Bhaskar K. Somani (Therapeutic Advances in Infectious Disease)
Background: Urinary tract infections (UTIs) are common and result in a significant impact on quality of life (QoL). Despite their prevalence, there seems to be a lack of evidence around patient-reported outcomes and measuring tools such as scoring systems and nomograms in UTIs. Patient-reported outcome measures (PROMs) help us measure patient-related symptoms and their QoL. Objective: Our literature review shows an up-to-date “atlas” of the available PROMs, nomograms and scoring systems that can help clinicians in treatment decisions and track treatment response in patients with UTIs. Design: Systematic review of the literature. Data sources and methods: A comprehensive systematic review was carried out on PubMed Medline, Scopus and CINAHL, according to PRISMA guidelines, using search terms related to PROMs, nomograms and scoring systems used in simple and complicated UTIs. A narrative review was done, and tool characteristics, accuracy, validation, and applicability were collected and summarized. Results: Sixty-two articles (with 16 different PROMs) were included in the final review. These included generic tools such as the 36-Item Short Form Health Survey and specific tools like the Acute Cystitis Symptom Score and Recurrent Urinary Tract Infection Impact Questionnaire, amongst others. While scoring systems seemed to be used for severe infections such as Fournier’s gangrene and emphysematous pyelonephritis, nomograms were primarily used for diagnosis and risk prediction. PROMs are useful tools and have utility within the management of patients with UTIs, but further clarity is needed as to which of these tools is most appropriate for each type of UTI as each offer their respective advantages and disadvantages. Conclusion: This atlas is the first comprehensive review of PROMs, scoring systems and nomograms in the management of UTIs. While PROMs improve patient care, further standardisation, external validation and accuracy are needed. While nomograms and scoring systems can help clinicians, these must be tailored to individual patients based on their specific clinical scenarios. Trial registration: PROSPERO registration number CRD42025625865.